INVESTOR PROTECTION THROUGH EXCHANGE TRANSACTION SETTLEMENT GUARANTEE AND INVESTOR PROTECTION FUND - Abubakar, Lastuti; Handayani, Tri (Faculty of Law Universitas Trunojoyo Madura, 2019)
Certainty and investors legal protection is the key to the success of capital market as financing and investment alternatives. To fulfill the international standards, Indonesia capital market regulation regulates the status of Clearing and Underwriter Institutions organized by Indonesian Clearing and Guarantee Corporation (KPEI) and serves to guarantee transactions settlement in Exchange as well as managing the Guarantee Fund. Other investor protection organized by the Indonesia Securities Investor Protection Fund (SIPF) formed to protect the assets of investors who lost and manage the Investor Protection Fund. This study aims to examine the position of KPEI as guaranteeing institution for the settlement of Exchange transactions to prevent settlement failures that can have systemic impacts, including how to optimize the management of Guarantee Funds. In addition, it was also examined how Indonesia SIPF could manage the Investor Protection Fund optimally in order to provide maximum protection. The method used is normative juridical with descriptive analytical research specifications. Data analysis used is qualitative juridical. Based on the results, KPEI is financial market infrastructure to prevent failure of potentially systemic transactions. Therefore, KPEI can be included as systemic financial institution. Either management of the Guarantee Fund by KPEI or Investor Protection Fund management by SIPF can use the trust concept to be able to increase the Guarantee Fund and Investor Protection Fund so that the guarantee of Exchange transaction settlement and investor protection is more certain and optimal.